ANALISIS PENGENDALIAN PERSEDIAN BAHAN BAKU TERHADAP EFISIENSI BIAYA PADA PT. MENARA CIPTA METALINDO - Subawa Subawa (JURNAL ADMINISTRASI KANTOR, 2015)
The title of this research is " Analysis of Raw Material Inventory Management Efficiency Cost Of At PT Menaracipta Metalindo "Objective: For Know What Is The Role of Inventory Control Raw Material Costs Against efficiency at PT Menaracipta Metalindo. Methods: Data collection method for preparation of this study, Field Method Using Risearch , for analysis technique used is the analysis of Economic Order Quantity (EOQ) , Analysis of TIC (Total Inventory Cost Analysis And RE orders Point. RESULTS: From the results obtained that the role of inventories of raw materials that the company is less efficient because it is based on calculations that have been done obtained total inventory cost of raw materials amounting to Rp 30.02385 million while the while the calculation using the EOQ method total inventory cost of materials Rp 24,010,997. It ii EOQ method more efficient means of Rp 5.92185 million. Therefore, the company should use EOQ method.